Intergenerational consequences of maternal domestic violence: Effect on nutritional status of children - Debayan Pakrashi; Sarani Saha (Global Labor Organization (GLO), 2020)
In this paper, we empirically estimate the causal impact of maternal domestic violence on the nutritional status of her children aged below five years. Using detailed dataset from the current and fourth round of the National Family Health Survey, we find robust evidence that violence experienced by mothers at the hands of her husband significantly increases the likelihood of her children being malnourished. When we focus on identifying the pathways through which domestic violence affect child health outcomes, we find that while domestic violence primarily affects child health via deterioration in maternal health, neglect of children in terms of inadequate provision of essential child care also seem to matter. The results from the heterogeneity analysis finally suggest that the detrimental effect of such violence is significantly less pronounced for children born to mothers who are currently working and are thus empowered.
Keywords: D19; I10; J12; 330; domestic violence; malnutrition; child health